2018
DOI: 10.1093/humrep/dey261
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic load, a measure of chronic physiological stress, is associated with pregnancy outcomes, but not fertility, among women with unexplained infertility

Abstract: Clinical Trials.gov number: NCT01044862.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
4
23
0
Order By: Relevance
“…Other indicators with VIP scores greater than 1 included depression, PDA-rated negative affect, anxiety, and PTSD symptoms. Across all 3 social support subscales with potential scores ranging from 0 to 40, PSYG had the lowest (17,18), PHSG next (22)(23)(24)(25)(26), and HG highest (26-29) (SI Appendix, Table S1 and Social Support and Outcomes. As social support indices were the strongest differentiators of the stress groups, we investigated if maternal stress group effects on our key perinatal outcomes would remain when controlling for the composite social support score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other indicators with VIP scores greater than 1 included depression, PDA-rated negative affect, anxiety, and PTSD symptoms. Across all 3 social support subscales with potential scores ranging from 0 to 40, PSYG had the lowest (17,18), PHSG next (22)(23)(24)(25)(26), and HG highest (26-29) (SI Appendix, Table S1 and Social Support and Outcomes. As social support indices were the strongest differentiators of the stress groups, we investigated if maternal stress group effects on our key perinatal outcomes would remain when controlling for the composite social support score.…”
Section: Resultsmentioning
confidence: 99%
“…Allostatic load (AL) incorporates multiple subclinical physiological/ physical parameters (e.g., diastolic and systolic blood pressure [BP], heart rate, body mass index [BMI], immune markers, and cortisol with consideration of relevant lifestyle factors [diet, exercise, and social support]) into a single index to measure the cumulative impact of "wear and tear" on the body of repeated activation, and associated dysregulation, of physiological systems stemming from chronically stressful situations (23,24). Higher AL during pregnancy is associated with increased odds of both PTB (25,26) and delivering a lowbirth-weight infant (25,27). Individual AL factors, including elevated maternal ambulatory BP and cortisol, have been associated with fetal neurodevelopment including lower resting FHR, increased FHR reactivity, and reduced FHR-movement coupling (28,29).…”
mentioning
confidence: 99%
“…We also know that female age has a prominent negative impact on fertility and the solutions are not simple, however, an alternative like validated dynamic models could predict both natural and ART-mediated in short time (15). Another study showed that allostatic load that is specific in chronic situation like infertility was not associated with fertility outcomes like conception, spontaneous abortion, and live birth (16). However, a cohort study on 4,999 couples showed that the prediction ranges could help in counselling couples for at least two years after their fertility work-up (17).…”
Section: Discussionmentioning
confidence: 99%
“… 10 15 35 The markers included are plasma leptin and IL-6 for the inflammatory domain, plasma cortisol for the neuroendocrine domain, and plasma LDL, HDL, FFA, triglycerides, fasting glucose, SBP and DBP for the cardiometabolic domain. 9 For HDL, the lowest quartile received the score of ‘1’, while the other quartiles received the score of ‘0’. For SBP and DBP, the clinical cut-off values were used: SBP greater than or equal to 120 mm Hg and DBP greater than or equal to 80 mm Hg were given the score of ‘1’.…”
Section: Methodsmentioning
confidence: 99%
“…The AL index is a composite score of subclinical physiological parameters that define AL, and this index has been associated with pregnancy outcomes such as preterm birth, 7 8 pre-eclampsia, 9 and small for gestational age (SGA). 10 However, it is unclear whether AL during pregnancy contributes to the development and progression of GDM and whether the AL index predicts adverse birth outcomes in GDM.…”
Section: Introductionmentioning
confidence: 99%